Role of physical activity in enhancing physical quality of life for stroke prevention - Satmyrza Mamikov; Zhanseri Ikram (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: stroke remains a leading cause of mortality and long-term disability worldwide. physical activity has been increasingly recognized as a modifiable lifestyle factor for improving health outcomes and preventing chronic diseases.